Not all price endings are created equal: Price points and asymmetric price rigidity - Daniel Levy; Avichai Snir; Alex Gotler; Haipeng (Allan) Chen (Journal of Monetary Economics, 2020)
We document an asymmetry in the rigidity of 9-ending prices relative to non-9-ending prices. Consumers have difficulty noticing higher prices if they are 9-ending, or noticing price-increases if the new prices are 9-ending, because 9-endings are used as a signal for low prices. Price setters respond strategically to the consumer-heuristic by setting 9-ending prices more often after price-increases than after price-decreases. 9-ending prices, therefore, remain 9-ending more often after price-increases than after price-decreases, leading to asymmetric rigidity: 9-ending prices are more rigid upward than downward. These findings hold for both transaction-prices and regular-prices, and for both inflation and no-inflation periods.
Keywords: L16; C91; E31; C93; D80; M31; 330; Asymmetric Price Adjustment; Sticky/Rigid Prices; 9-Ending Prices; Psychological Prices; Price Points; Regular/Sale Prices